Sleep Less, Weigh More: Unraveling the Sleep-Obesity Connection in Adult - Az’yan Nazwa Maharani Putri; Rahmah Dwi Yuliyanti; Almira Sitasari; Agus Wijanarka; Jutharat Attawet; Tri Siswati (Ficco Public Health Journal, 2025)
Background: Obesity is an increasingly complex and common global health problem, especially among adults. The aim of this scoping review is to examine the relationship between sleep duration and obesity in adults.  Methods: A scoping review was conducted following the Joanna Briggs Institute (JBI) methodology guideline. Databases including PUBMED, ScienceDirect, DOAJ, and ResearchGate were searched in 2024 with the keywords "obesity AND sleep AND adults". Articles published between 2019 and 2023 that focused on observational studies. Results: Of the 2960 articles found, 7 articles met the inclusion criteria. A cross-sectional research design was used by 86% of the studies, while only 14% were enrolled in cohort studies. The majority of studies showed a significant correlation between short-term and long-term sleep duration and the likelihood of becoming obese. The assessment tools used were extensive and included interviews, questionnaires, and sleep monitors such as the Actiwatch Spectrum. The obesity assessment indicators used are Body Mass Index (BMI) and waistline. Conclusions: The review suggests that adults whose sleep is too short or too long are more likely to be obese. Lack of sleep can trigger hormonal changes, stimulate appetite, and result in obesity.